2007
DOI: 10.1159/000099201
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nebivolol and Metoprolol on Inflammatory Mediators in Human Coronary Endothelial or Smooth Muscle Cells. Effects on Neointima Formation After Balloon Denudation in Carotid Arteries of Rats Treated with Nebivolol

Abstract: Objective and Background: Inflammation plays a critical role in all stages of atherogenesis. Proliferating vascular smooth muscle cells (SMC) and endothelial cells (EC) enhancing the inflammatory response, both contribute to the progression of atherosclerosis. Anti-proliferative, anti-inflammatory and anti-oxidative therapy seems to be a promising therapeutic strategy. The aim of this study was to assess the anti-proliferative and anti-inflammatory effect of the β-blocker nebivolol in comparison to metoprolol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 30 publications
3
17
0
2
Order By: Relevance
“…Moreover, atherosclerotic plaque formation in the aortic root as well as reactive oxygen species (ROS) production was decreased or even normalized by nebivolol, whereas metoprolol had less or no effects. These results are consistent with recent findings indicating the beneficial role of nebivolol on endothelial function in different animal models (Oelze et al, 2006;Wolf et al, 2007). Comparable effects could be observed in the penile tissue.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, atherosclerotic plaque formation in the aortic root as well as reactive oxygen species (ROS) production was decreased or even normalized by nebivolol, whereas metoprolol had less or no effects. These results are consistent with recent findings indicating the beneficial role of nebivolol on endothelial function in different animal models (Oelze et al, 2006;Wolf et al, 2007). Comparable effects could be observed in the penile tissue.…”
Section: Discussionsupporting
confidence: 93%
“…The inhibition of MCP-1 secretion in vascular smooth muscle cells by nebivolol might therefore reduce monocyte recruitment and slow down plaque formation. This reduction in inflammatory cells in combination with reduced plaque size could be demonstrated for nebivolol treated rats after carotid artery denudation [34].…”
Section: Discussionmentioning
confidence: 59%
“…Recent research has shown that beta-blockers appear to have only a minimal (nebivolol) or no effect (metoprolol) on proinflammatory genes in endothelial cells [233]. In contrast, in another study carvedilol (a beta-blocker well known for its anti-inflammatory and antioxidant properties) [234] was found to suppress plasma levels of TNF-α and IL-6 in ischemic and nonischemic dilated cardiomyopathy, but with effects more marked in nonischemic patients [235].…”
Section: Pathophysiology Of the Inflammatory Response In Heart Failurementioning
confidence: 99%